Augmenting performance feedback does not affect 4 km cycling time-trials in the heat - Waldron, M.; Villerius, V.; Murphy, A. (Journal of Sports Sciences, 2015)
We compared the effects of (1) accurate and (2) surreptitiously augmented performance feedback on power output and physiological responses to a 4000 m time-trial in the heat. Nine cyclists completed a baseline (BaseL) 4000 m time-trial in ambient temperatures of 30°C, followed by two further 4000 m time-trials at the same temperature, randomly assigning the participants to an accurate (ACC; accurate feedback of baseline) or deceived (DEC; 2% increase above baseline) feedback group. The total power output (PO) and aerobic (Paer) and anaerobic (Pan) contributions were determined at 0.4 km stages during the time-trials, alongside measurements of rectal (Trec) and skin (Tskin) temperatures. There were no differences (P > 0.05) in any of the variables between BaseL, ACC and DEC, despite increases (P < 0.05) in Trec and Tskin. Typical pacing profiles were demonstrated; however, there was no interaction (P > 0.05) between feedback condition and time-trial stage. Providing surreptitiously augmented performance feedback to well-trained cyclists did not alter their performance or physiological responses to a 4000 m time-trial in a hot environment. The assumed influence of augmented performance feedback was nullified in the heat, perhaps reflecting a central down-regulation of exercise intensity in response to an increased body temperature.